2010
DOI: 10.1186/1476-069x-9-62
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol a exposure in Mexico City and risk of prematurity: a pilot nested case control study

Abstract: BackgroundPresence of Bisphenol A (BPA) has been documented worldwide in a variety of human biological samples. There is growing evidence that low level BPA exposure may impact placental tissue development and thyroid function in humans. The aim of this present pilot study was to determine urinary concentrations of BPA during the last trimester of pregnancy among a small subset of women in Mexico City, Mexico and relate these concentrations to risk of delivering prematurely.MethodsA nested case-control subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
84
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 50 publications
16
84
3
2
Order By: Relevance
“…1 The use of BPA-containing products in daily life makes exposure ubiquitous in industrialized and industrializing countries. [2][3][4][5] The predominant source of BPA exposure for most people is diet, although exposure also might occur through inhalation or dermal absorption, which results in substantial exposure among persons involved in the manufacture or handling of BPAcontaining products. [6][7][8][9][10] BPA might disrupt the endocrine system.…”
mentioning
confidence: 99%
“…1 The use of BPA-containing products in daily life makes exposure ubiquitous in industrialized and industrializing countries. [2][3][4][5] The predominant source of BPA exposure for most people is diet, although exposure also might occur through inhalation or dermal absorption, which results in substantial exposure among persons involved in the manufacture or handling of BPAcontaining products. [6][7][8][9][10] BPA might disrupt the endocrine system.…”
mentioning
confidence: 99%
“…2 BPA shows affinity for the estrogen receptor and may alter its function by blocking or mimicking the action of estrogen. 3 Previous epidemiological studies have reported the associations between BPA exposure and adverse health effects on the reproductive [4][5][6][7][8] and endocrine systems. 9 BPA exposure had also been associated with cardiovascular disorders.…”
mentioning
confidence: 99%
“…[4][5][6] Epidemiological studies have suggested that BPA could have adverse effects on human health. 7 Specifically, BPA exposure has been shown to be associated with increased production of liver enzymes, 8 recurrent miscarriages, 9 premature delivery of fetuses, 10 inflammation and oxidative stress, 11 decreased quality of semen, 12,13 and male sexual dysfunction. 14 In 2008, Lang et al 8 conducted a study investigating the associations between past history of chronic diseases and BPA concentration by analyzing data sets from the National Health and Nutrition Examinations Survey.…”
mentioning
confidence: 99%